2006
DOI: 10.1073/pnas.0602425103
|View full text |Cite
|
Sign up to set email alerts
|

The circadian basis of winter depression

Abstract: The following test of the circadian phase-shift hypothesis for patients with winter depression (seasonal affective disorder, or SAD) uses low-dose melatonin administration in the morning or afternoon͞evening to induce phase delays or phase advances, respectively, without causing sleepiness. Correlations between depression ratings and circadian phase revealed a therapeutic window for optimal alignment of circadian rhythms that also appears to be useful for phase-typing SAD patients for the purpose of administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
272
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(298 citation statements)
references
References 39 publications
9
272
1
4
Order By: Relevance
“…Clinical response to mood stabilizers is not uniform: only about 1/3 of BD patients respond fully to lithium, and the clinical profiles that predict lithium vs. VPA response differ considerably (McCarthy et al, 2010). Accordingly, while many studies have reported a predisposition towards phase delay/long periods in BD, some have reported phase advance/short period in BD (Kripke et al, 1978;Salvatore et al, 2008) or other mood disorders (Lewy et al, 2006). Perhaps only a subset of patients with long period/phase delay benefit from the period-shortening effects of VPA, while a different subset with short period/phase advance benefit from lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical response to mood stabilizers is not uniform: only about 1/3 of BD patients respond fully to lithium, and the clinical profiles that predict lithium vs. VPA response differ considerably (McCarthy et al, 2010). Accordingly, while many studies have reported a predisposition towards phase delay/long periods in BD, some have reported phase advance/short period in BD (Kripke et al, 1978;Salvatore et al, 2008) or other mood disorders (Lewy et al, 2006). Perhaps only a subset of patients with long period/phase delay benefit from the period-shortening effects of VPA, while a different subset with short period/phase advance benefit from lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the early morning light is leading to a phase advance in the circadian system putting it back on track with the sleep/wake cycle. In addition, there have been reports that melatonin therapy in the evening can also be effective in producing this same phase advance and may help with the treatment of SAD (Lewy et al, 1998a;Lewy et al, 2006). Though this theory has a lot of support, it still remains controversial.…”
Section: Seasonal Affective Disordermentioning
confidence: 99%
“…However, in some studies, evening light exposure has an equally strong antidepressant effect as morning exposure and several studies find no therapeutic effects of melatonin treatment (Wirz-Justice et al, 1990;Wirz-Justice et al, 1993;Terman et al, 2001). Other theories suggest that SAD patients actually fall into two categories, some with a phase delay in rhythms and some with a phase advance in rhythms (Boivin, 2000;Lewy et al, 2006). The timing of light therapy and perhaps melatonin therapy would then need to be adjusted for each group separately to produce the desired shift in rhythms and therapeutic effects.…”
Section: Seasonal Affective Disordermentioning
confidence: 99%
“…Most SAD patients become depressed in the winter time because of the later dawn, which leads their circadian rhythms to delay with respect to both clock time and to the sleep-wake cycle [45]. Changes in the latter sleep-wake are apparent, with most patients presenting hypersomnia in conjunction with EDS.…”
Section: Depression and Circadian Rhythmsmentioning
confidence: 99%